Graphene quantum dot nano material and preparation method thereof

By dispersing metal oxides to the surface of graphene/graphene quantum dots, the problem of easy agglomeration of graphene is solved, and the retention of graphene characteristics and the improvement of metal oxide performance is achieved.

CN119797351APending Publication Date: 2025-04-11GUANGZHOU SHUNZHUO ENERGY TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510085447.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Graphene/graphene quantum dots have high surfactivity and are prone to agglomeration, resulting in loss of characteristics.

Method used

The metal oxide is dispersed onto the graphene/graphene quantum dot surface to make graphene quantum dot nanocomposites, which ensure dispersion and characteristics retention through ultrasonic mixing and calcining steps.

Benefits of technology

It effectively weakens the interaction between graphene sheet layers, retains the characteristics of graphene, and improves the cycling performance and capacitance of metal oxides.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005250001250000071
    Figure BDA0005250001250000071
Patent Text Reader

Abstract

The invention discloses a graphene quantum dot nano material and a preparation method thereof, and the graphene quantum dot nano material at least comprises the following preparation raw materials in parts by weight: 1-30 parts of graphene, 1-30 parts of graphene oxide quantum dots, 70-100 parts of metal oxide and 30-50 parts of a dispersing agent. Graphene with a specific specific surface area and graphene oxide quantum dots with a specific particle size are selected and compounded for use, so that graphene is fully reduced, metal oxides are not agglomerated, and in addition, reduction of graphene oxide can be promoted by controlling a proper pH value in the system. The graphene quantum dot nano material can effectively improve the cycle performance, the rate capability and the capacitance of an oxide as a battery electrode, and reduce the impedance of the oxide. In addition, the preparation method is simple in preparation process, low in cost and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite nanomaterials, and in particular to a graphene quantum dot nanomaterial and a preparation method thereof. Background Art

[0002] Graphene is a sp 2 A new material in which hybrid connected carbon atoms are tightly stacked into a single-layer two-dimensional honeycomb lattice structure. It has excellent optical, electrical, and mechanical properties, and has important application prospects in materials science, micro-nano processing, energy, biomedicine, and drug delivery. It is considered to be a revolutionary material in the future. Since its discovery in 2004, this material has received widespread attention from the world's scientific and engineering communities. Graphene is currently the thinnest and hardest material in the world, with extremely low light absorption (2-3%), extremely high thermal conductivity (5300W / mk) and electron mobility (15000cm2 / vs), extremely low resistivity (10-6Ω / cm), and extremely high mechanical strength (100 times that of steel).

[0003] Graphene quantum dots (GQDs), as graphene zero-dimensional nanomaterials, also have some unique advantages such as band gaps caused by quantum confinement, good dispersibility, richer active sites (edges, functional groups, dopants, etc.), biocompatibility, better adjustability of chemical and physical properties, and sizes comparable to those of biological molecules.

[0004] By combining it with other materials, such as metal oxides, it can be widely used in energy storage and energy conversion fields, such as photocatalytic materials, photovoltaic materials, hydrogen storage materials, lithium-ion batteries and supercapacitor electrode materials. However, in practical applications, due to the extremely high surface activity of graphene / graphene quantum dots and their easy aggregation, graphite particles are formed after aggregation, which easily loses the above characteristics.

[0005] The present invention aims to provide a graphene quantum dot nanomaterial, which disperses metal oxides on the surface of graphene / graphene quantum dots to make a graphene quantum dot nanocomposite material, which can increase the spacing between graphene sheets to several nanometers, thereby greatly weakening the interaction between graphene sheets and retaining the characteristics of graphene. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present invention provides a graphene quantum dot nanomaterial. The preparation raw materials include at least 1-30 parts of graphene, 1-30 parts of graphene oxide quantum dots, 70-100 parts of metal oxide, and 30-50 parts of dispersant, by weight.

[0007] As a preferred technical solution, the preparation raw materials include at least 1-20 parts of graphene, 1-20 parts of graphene oxide quantum dots, 70-80 parts of metal oxide, and 40-50 parts of dispersant, by weight.

[0008] As a preferred technical solution, the specific surface area of ​​the graphene is 110-200m 2 / g.

[0009] As a preferred technical solution, the particle size of the graphene is 0.06-0.12 μm.

[0010] As a preferred technical solution, the particle size of the graphene oxide quantum dots is less than 15 nm.

[0011] As a preferred technical solution, the metal oxide is at least one of zinc oxide, iron oxide, titanium oxide, manganese oxide, aluminum oxide, lithium oxide, nickel oxide, and tin oxide.

[0012] As a preferred technical solution, the particle size of the zinc oxide is 15-100 nm.

[0013] As a preferred technical solution, the particle size of the titanium oxide is 10-60 nm.

[0014] The second aspect of the present invention also provides a method for preparing the graphene quantum dot nanomaterial as described above, comprising the following steps:

[0015] S1, dissolving graphene and graphene oxide quantum dots in a dispersant to prepare a graphene and graphene oxide quantum dot dispersed solution;

[0016] S2, adding metal oxide to the dispersed solution of graphene and graphene oxide quantum dots, ultrasonically mixing, reacting for 24-30 hours, filtering, washing, drying, and calcining at 400-600° C. for 2-4 hours under an inert gas atmosphere to obtain.

[0017] As a preferred technical solution, in step S1, the pH value of the graphene and graphene oxide quantum dot dispersion solution is 7-8.

[0018] Beneficial Effects

[0019] 1. The present invention utilizes the good water solubility of graphene oxide quantum dots to form a composite material of graphene / metal oxide that is evenly dispersed in the final product.

[0020] 2. The present invention selects a compound of graphene with a specific specific surface area and graphene oxide quantum dots with a specific particle size to fully reduce the graphene without causing agglomeration of the metal oxide. In addition, controlling an appropriate pH value in this system can promote the reduction of graphene oxide.

[0021] 3. The present invention uses graphene and graphene oxide quantum dots as reaction precursors, which can make the metal oxide more evenly dispersed on the graphene surface and have better dispersibility, and can completely solve the problem of poor dispersibility.

[0022] 4. In the present invention, metal oxides are compounded with compounds of different particle sizes to make the compounding with graphene / graphene oxide quantum dots more uniform.

[0023] 5. The graphene quantum dot nanomaterials described in the present invention can effectively improve the cycle performance, rate performance, and capacitance of oxides as battery electrodes, and reduce their impedance.

[0024] 6. The preparation method of the present invention has simple preparation process, low cost and can be applied to large-scale production. DETAILED DESCRIPTION

[0025] The content of the present invention can be more easily understood by selecting the following detailed description of the preferred implementation method of the present invention and the embodiments included. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs. When there is a conflict, the definition in this specification shall prevail.

[0026] In order to solve the above problems, the first aspect of the present invention provides a graphene quantum dot nanomaterial. The preparation raw materials include at least 1-30 parts of graphene, 1-30 parts of graphene oxide quantum dots, 70-100 parts of metal oxide, and 30-50 parts of dispersant, by weight.

[0027] In some preferred embodiments, the preparation raw materials include at least 1-20 parts of graphene, 1-20 parts of graphene oxide quantum dots, 70-80 parts of metal oxide, and 40-50 parts of dispersant, by weight.

[0028] In some preferred embodiments, the specific surface area of ​​the graphene is 110-200 m 2 / g.

[0029] In some preferred embodiments, the graphene has a particle size of 0.06 to 0.12 μm.

[0030] In some preferred embodiments, the particle size of the graphene oxide quantum dots is less than 15 nm.

[0031] In some preferred embodiments, the metal oxide is at least one of zinc oxide, iron oxide, titanium oxide, manganese oxide, aluminum oxide, lithium oxide, nickel oxide, and tin oxide.

[0032] In some more preferred embodiments, the metal oxide is at least one of zinc oxide, titanium oxide, manganese oxide, and aluminum oxide.

[0033] In some more preferred embodiments, the metal oxide is zinc oxide or titanium oxide.

[0034] In some more preferred embodiments, the mass ratio of zinc oxide to titanium oxide is 1-2:2-3.

[0035] In some more preferred embodiments, the zinc oxide has a particle size of 15-100 nm.

[0036] In some more preferred embodiments, the particle size of the titanium oxide is 10-60 nm.

[0037] In some preferred embodiments, the dispersant is at least one of deionized water, ethylene glycol, and isopropanol.

[0038] The second aspect of the present invention also provides a method for preparing the graphene quantum dot nanomaterial as described above, comprising the following steps:

[0039] S1, dissolving graphene and graphene oxide quantum dots in a dispersant, adjusting the pH to 7-8 with sodium hydroxide, and obtaining a graphene and graphene oxide quantum dot dispersed solution;

[0040] S2, adding metal oxide to the graphene and graphene oxide quantum dot dispersion solution, ultrasonically mixing, reacting for 24-30 hours, filtering, washing with deionized water 2-3 times, drying, and calcining at 400-600° C. for 2-4 hours under a nitrogen atmosphere to obtain the graphene quantum dot nanomaterial.

[0041] Example

[0042] The technical scheme of the present invention is described in detail below by way of examples, but the protection scope of the present invention is not limited to the examples. Unless otherwise specified, the raw materials in the present invention are all commercially available.

[0043] Example 1

[0044] Example 1 provides a graphene quantum dot nanomaterial. The preparation raw materials include at least 1 part of graphene, 30 parts of graphene oxide quantum dots, 70 parts of metal oxides, and 30 parts of dispersants, by weight.

[0045] The specific surface area of ​​the graphene is 150-200m 2 / g, particle size of 0.06-0.12 μm (available from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, model: TNERGO).

[0046] The particle size of the graphene oxide quantum dots is less than 15 nm (available from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., model: XF042-1).

[0047] The metal oxides are zinc oxide and titanium oxide, and the mass ratio of the metal oxides is 1:2.

[0048] The particle size of the zinc oxide is 15 nm (available from Beijing Dekedaojin Technology Co., Ltd., model: DK-ZnO-15).

[0049] The particle size of the titanium oxide is 60 nm (available from Beijing Dekedaojin Technology Co., Ltd., model: DK-TiO2-60).

[0050] The dispersant is ethylene glycol.

[0051] This example also provides a method for preparing the graphene quantum dot nanomaterial as described above, comprising the following steps:

[0052] S1, dissolving graphene and graphene oxide quantum dots in a dispersant, adjusting the pH to 7-8 with sodium hydroxide, and obtaining a graphene and graphene oxide quantum dot dispersed solution;

[0053] S2, adding metal oxide to the graphene and graphene oxide quantum dot dispersion solution, ultrasonically mixing, reacting for 24 hours, filtering, washing with deionized water for 3 times, drying, and calcining at 400° C. for 4 hours under a nitrogen atmosphere to obtain the graphene quantum dot nanomaterial.

[0054] Example 2

[0055] Example 2 provides a graphene quantum dot nanomaterial. The preparation raw materials include at least 30 parts of graphene, 1 part of graphene oxide quantum dots, 100 parts of metal oxides, and 50 parts of dispersants, by weight.

[0056] The specific surface area of ​​the graphene is 150-200m 2 / g, particle size of 0.06-0.12 μm (available from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, model: TNERGO).

[0057] The particle size of the graphene oxide quantum dots is less than 15 nm (available from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., model: XF042-1).

[0058] The metal oxides are zinc oxide and titanium oxide, and the mass ratio of the metal oxides is 2:3.

[0059] The particle size of the zinc oxide is 100 nm (available from Beijing Dekedaojin Technology Co., Ltd., model: DK-ZnO-100).

[0060] The particle size of the titanium oxide is 10 nm (available from Beijing Dekedaojin Technology Co., Ltd., model: DK-TiO2-A10).

[0061] The dispersant is isopropyl alcohol.

[0062] This example also provides a method for preparing the graphene quantum dot nanomaterial as described above, comprising the following steps:

[0063] S1, dissolving graphene and graphene oxide quantum dots in a dispersant, adjusting the pH to 7-8 with sodium hydroxide, and obtaining a graphene and graphene oxide quantum dot dispersed solution.

[0064] S2, adding metal oxide to the graphene and graphene oxide quantum dot dispersion solution, ultrasonically mixing, reacting for 30 hours, filtering, washing with deionized water twice, drying, and calcining at 600° C. for 2 hours under a nitrogen atmosphere to obtain the graphene quantum dot nanomaterial.

[0065] Example 3

[0066] Example 3 provides a graphene quantum dot nanomaterial. The preparation raw materials include at least 5 parts of graphene, 10 parts of graphene oxide quantum dots, 70 parts of metal oxide, and 40 parts of dispersant, by weight.

[0067] The specific surface area of ​​the graphene is 150-200m 2 / g, particle size of 0.06-0.12 μm (available from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, model: TNERGO).

[0068] The particle size of the graphene oxide quantum dots is less than 15 nm (available from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., model: XF042-1).

[0069] The metal oxides are zinc oxide and titanium oxide, and the mass ratio of the metal oxides is 1.5:2.5.

[0070] The particle size of the zinc oxide is 30 nm (available from Beijing Dekedaojin Technology Co., Ltd., model: DK-ZnO-30).

[0071] The particle size of the titanium oxide is 20 nm (available from Beijing Dekedaojin Technology Co., Ltd., model: DK-TiO2-20).

[0072] The dispersant is deionized water and ethylene glycol, and the volume ratio of the two is 1:2.

[0073] This example also provides a method for preparing the graphene quantum dot nanomaterial as described above, comprising the following steps:

[0074] S1, dissolving graphene and graphene oxide quantum dots in a dispersant, adjusting the pH to 7-8 with sodium hydroxide, and obtaining a graphene and graphene oxide quantum dot dispersed solution;

[0075] S2, adding metal oxide to the graphene and graphene oxide quantum dot dispersion solution, ultrasonically mixing, reacting for 26 hours, filtering, washing with deionized water for 3 times, drying, and calcining at 500° C. for 3 hours under a nitrogen atmosphere to obtain the graphene quantum dot nanomaterial.

[0076] Comparative Example 1

[0077] The specific surface area of ​​the graphene is changed to 50-80m 2 / g, particle size is 1-5 μm (can be purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, model: TNERGO-3), and the rest is the same as Example 3.

[0078] Comparative Example 2

[0079] The specific surface area of ​​the graphene is changed to 70-110 m 2 / g, particle size is 8-15 μm (can be purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, model: TNERGO-10), and the rest is the same as Example 3.

[0080] Comparative Example 3

[0081] The specific surface area of ​​the graphene is changed to 110-170m 2 / g, particle size>50 μm (can be purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, model: TNERGO-50), and the rest is the same as in Example 3.

[0082] Comparative Example 4

[0083] The metal oxide is changed to zinc oxide, and the rest is the same as in Example 3.

[0084] Comparative Example 5

[0085] The metal oxide is replaced by titanium oxide, and the rest is the same as in Example 3.

[0086] Comparative Example 6

[0087] The particle size of the titanium oxide was changed to 5 nm (available from Beijing Dekedaojin Technology Co., Ltd., model: T5), and the rest was the same as in Example 3.

[0088] Performance Testing

[0089] 1. The nanomaterials obtained in Examples 1 to 3 and Comparative Examples 1 to 6 were filled into the positive electrode material of the lithium battery, and the metal lithium sheet was used as the negative electrode. The battery was subjected to a charge and discharge cycle test using a LAND battery test system at room temperature. The test voltage was 3.0-4.4V, and the current density was 0.5-1C. The test results are shown in Table 1. Among them, the capacity retention rate after 150 cycles was higher than 90% and was excellent, 70-80% was good, and lower than 70% was fair.

[0090] Table 1

[0091]

[0092] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A graphene quantum dot nanomaterial, characterized in that: By weight, the preparation raw materials include at least 1-30 parts of graphene, 1-30 parts of graphene oxide quantum dots, 70-100 parts of metal oxide, and 30-50 parts of dispersant.

2. The graphene quantum dot nanomaterial according to claim 1, characterized in that: By weight, the preparation raw materials include at least 1-20 parts of graphene, 1-20 parts of graphene oxide quantum dots, 70-80 parts of metal oxide, and 40-50 parts of dispersant.

3. The graphene quantum dot nanomaterial according to claim 1 or 2, characterized in that: The specific surface area of ​​the graphene is 110-200m 2 / g.

4. The graphene quantum dot nanomaterial according to claim 3, characterized in that: The particle size of the graphene is 0.06-0.12 μm.

5. The graphene quantum dot nanomaterial according to claim 4, characterized in that: The particle size of the graphene oxide quantum dots is less than 15 nm.

6. The graphene quantum dot nanomaterial according to claim 3, characterized in that: The metal oxide is at least one of zinc oxide, iron oxide, titanium oxide, manganese oxide, aluminum oxide, lithium oxide, nickel oxide and tin oxide.

7. The graphene quantum dot nanomaterial according to claim 6, characterized in that: The particle size of the zinc oxide is 15-100 nm.

8. The graphene quantum dot nanomaterial according to claim 3, characterized in that: The particle size of the titanium oxide is 10-60 nm.

9. A method for preparing the graphene quantum dot nanomaterial according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, dissolving graphene and graphene oxide quantum dots in a dispersant to prepare a graphene and graphene oxide quantum dot dispersed solution; S2, adding metal oxide to the dispersed solution of graphene and graphene oxide quantum dots, ultrasonically mixing, reacting for 24-30 hours, filtering, washing, drying, and calcining at 400-600° C. for 2-4 hours under an inert gas atmosphere to obtain.

10. The method for preparing graphene quantum dot nanomaterial according to claim 9, characterized in that: In step S1, the pH value of the graphene and graphene oxide quantum dot dispersion solution is 7-8.

Citation Information

Patent Citations

  • Graphene and graphene quantum dot and metallic oxide or phosphate nanocomposite material and preparation method thereof

    CN104591167A

  • Preparation method of graphene quantum dot composite material for lead-acid battery

    CN114759170A

  • Method for preparing graphene based quantum dots, graphene based quantum dots prepared by the same and application devices using the same

    KR101440226B1

  • Method for synthesizing graphene-based nanocomposite and graphene-based nanocomposite systnesized using the method

    US20150064442A1

  • Graphene quantum dot-carbon material composites and their use as electrocatalysts

    US20150280248A1